Mechanical design of machine elements - Çakır, Özgen Ümit Çolak (İstanbul: Literatür Yayıncılık)
Mechanical Design of Machine Elements book is the English translation of the book on Project Design of Machine Elements (Makina Elemanlarının Projelendirilmesi) by Atilla Bozaci, Ozgen Colak Cakır and Ilknur Kocas. However, it is not a literal translation. Various additions and changes have been made in this version.The book has not been prepared with a textbook understanding and technique. It is not intended to introduce a certain machine element in details to students who do not have sufficient prior knowledge on the subject. It is prepared for students who have taken or are taking machine elements courses after taking materials and strength courses, and engineers working in the field of application. Information and suggestions that can be found in detail but separately in textbooks or various sources on machine elements are summarized and arranged in this book. At the beginning, after each topic was summarized with this understanding, table values, diagrams and standard values that a student or engineer doing a project work on this subject might need were partially summarized and brought together. After each topic, application examples were given in a style reminiscent of project studies. Students completing a machine element course using this book should be able to execute original designs for machine elements and integrate the elements into a system composed of several elements. This book consists of thirteen chapters. These are: mechanical design of machine elements under dynamic loads, shaft and axles, shaft and hub connections (keys and press fit), threaded fasteners, riveted fasteners, welding, brazing and bonding, springs, couplings, lubrication technique, journal bearings, rolling element bearings, belt-pulley mechanisms and gear mechanisms. Contents; Mechanical Desing of Machine Elements Under Dynamic Loads Shafts and Axles Shaft and Hub Connections Press Fit Threaded Fasteners Riveted Fasteners Welding, Brazing and Bonding Springs Couplings Lubrication Technique, Journal Bearings Rolling Element Bearings Belt-Pulley Mechanisms Gears
2
Keywords: Makina